Upaya Peningkatan Output Produksi Proses Core Coil pada PT. XYZ - Shelina Evelyn Rampengan; Felecia Felecia; Karina Agustin (Jurnal Titra, 2022)
PT. XYZ is a company that produces distribution transformers that have a problem with insufficient production output of the company. Based on company data, the company's target is 372 units/month. Meanwhile, the company's capacity is 207 units/month, which comes from the longest process, namely coil LV. The production capacity problem can be solved by improving the process whose capacity does not reach the target, namely the coil LV and Core Coil Assembly  (CCA). Improvements that are the first priority are the coil LV process as the longest process and increasing the capacity of the CCA process. The proposed alternative for improvement is to add 3 coil LV operators to 11 people and do overtime for 6 operators for 1 day and divide the work elements of the CCA helper. The cost that needs to be spent for the proposal is Rp 14,496,000. The alternative proposals submitted by the authors have also been validated and verified in simulations using ProModel by producing outputs that are close to the company's target.